CSAMT constraints on the metallogenic mechanism of the Zhaishang gold deposit, West Qinling, China. Issue 4 (4th July 2022) - Xu, Liuyang; Yin, Yaotian; Jin, Sheng; Wei, Wenbo; Hao, Ziqiong; Li, Xinbin; Liu, Hanyuan; Li, Han
Abstract : Whether the ore-forming fluids and materials of Zhaishang Carlin/Carlin-like type gold deposit were derived from concealed Mesozoic intermediate–acidic intrusive rocks through deep faults is controversial. In this study, eight CSAMT profiles were used to investigate the electrical resistivity structure of this deposit using high-resolution 2-D inversion. A ∼1 km wide high-resistivity (>3000 Ωm) body was observed at the base of the resistivity model (∼600 m). Two slightly NE-dipping high-conductivity channels were also observed along two sides of the high-resistivity body that connected to the gold-bearing quartz veins at the surface. The data suggest that the high-resistivity body is a Mesozoic granite and the two high-conductivity channels are fault zone conductors, which may be the wings of an NE-trending anticline that formed under regional compressive stress during the Caledonian orogeny. Their reactivation during the Indosinian and Yanshanian periods likely formed conduits for rising deeply-sourced ore-forming fluids (likely magmatic water). These conduits also promoted ground and meteoric water infiltration and mixing with the rising fluids. Accordingly, at least some of the ore-forming fluids and materials in the Zhaishang deposit were derived from Mesozoic granites through concealed faults, which can provide new geophysical constraints for discussions of the deposit's metallogenic mechanism.